The long and sinuous path of the Faculty Of Law of The Pontifical Catholic University Of Peru - Ramos Núñez, Carlos (2016)
Since its foundation, the Faculty of Law of the Pontifical Catholic University of Peru has come a long way full of pleasant and adverse events, which have allowed it to become a major center of studies and knowledge. In this article, the author studies and analyzes the most important events of the Law School, among these are emblematic and historical characters, transcendent events and reforms.